Systems Biology Functional Strategies of Living Organisms - Konieczny, Leszek; Roterman-Konieczna, Irena; Spólnik, Paweł (Springer International Publishing : Imprint: Springer, 2014)
The objective of this book is to present the strategies employed by living organisms on a molecular level and to help understand the basics of Systems Biology. Its content is organized in a way to meet the exponential growth in the volume of biological knowledge, and the need for a multidisciplinary approach in the practice of teaching modern biology. For this reason, the whole material is divided into five chapters, each devoted to a fundamental concept: Structure-Function, Energy, Information, Regulation and Interrelationships. The book describes generic mechanisms which occur in biology and promotes a simulation-based approach to the subject of Systems Biology. The use of basic knowledge as the background for presenting biological problems obligates the teachers to deal with generalized phenomena comprising the ever increasing volume of teaching materials. This book is intended for biologists and is informative for specialists in the areas of computer science, robotics and engineering.